Linguistic Analysis of Witness Statements in Litigations - Miškulin-Saletović, Lucia; Kišiček, Gabrijela (2009)
The aim of the research was to determine to what functional style(s) of the Croatian language belong witness statements in litigations. The research was based on the theoretical division of the Croatian language into four functional styles (literary-artistic style, scientific style, conversational style and administrative style). The starting hypothesis was that witness statements will, due to the interaction-situational context, contain not only elements of the administrative style, but also elements of the conversational style, since witness statements are given by laymen who found themselves in courtroom settings. Apart from that we believed that we would find certain distinct linguistic characteristics of witness statements as a separate text type. The research covered 30 witness statements, whose lexical and syntactical level was analyzed. The research results showed that witness statements possess certain characteristics of the conversational style (usage of dialect words, idioms and elliptical sentences) and of the administrative style (pleonasms, stereotyped speech, replacement of full verbs with functional verbs and verbal nouns … ). We have also discovered specific characteristics of witness statements as a separate text type that are related to the function(s), subject and the interaction-communicative process. Some of the mentioned characteristics are the usage of the simple present tense and simple perfect tense, and no simple future tense (that is mentioned in the literature as one of the characteristics of the administrative style) and the usage of the pronominal adjective isti, ista (the aforesaid). We have also determined the constant usage of typical vocabulary (imovinsko-pravno (property rights), optant (optant), imovinski postupak (property litigation), iskazati (give sworn evidence), predmetna kuća (the house in question) … .). The sentences are long and contain additional descriptions, while exactly the opposite is characteristic of the administrative and conversational style. The research has shown that witness statements are a separate text type with their own specific linguistic characteristics, strongly influenced by their function, topic and interaction-situational context.
Projekt MZOS
ENG